2022
DOI: 10.3390/jcm11123426
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Variations in Retinal Parameters after Uncomplicated Cataract Surgery

Abstract: Background: Cataract phacoemulsification surgery provides excellent refractive results; however, it also elicits changes in the posterior segment of the eye. This study aimed to determine changes in retinal parameters measured by spectral-domain optical coherence tomography (SD-OCT) and OCT angiography (OCTA) after an uncomplicated cataract surgery, including the impact of effective phacoemulsification time (EPT). Methods: The study included 44 patients without retinal abnormalities, followed up after unilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
3
3
0
Order By: Relevance
“…Therefore, in agreement with our findings, most of the previous studies have shown that there is a postoperative increase of retinal capillary plexus lasting for at least 3 months [8,9,17,18], with one study [23] demonstrating preservation of the changes for up to 1 year, while another study [15] showed very limited, less than 3 months, effect.…”
Section: Fig 2 Example Of a Patient Showing Upregulation Of Retinal F...supporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, in agreement with our findings, most of the previous studies have shown that there is a postoperative increase of retinal capillary plexus lasting for at least 3 months [8,9,17,18], with one study [23] demonstrating preservation of the changes for up to 1 year, while another study [15] showed very limited, less than 3 months, effect.…”
Section: Fig 2 Example Of a Patient Showing Upregulation Of Retinal F...supporting
confidence: 93%
“…Similar results with persistence of increased macular vessel density and thickness one to three months following cataract surgery, were observed in previous studies [8,9,23]. The study with the longest 12 months follow up so far, is the one by Gawęcki M et al [23] with postoperative evaluation with OCT-A of 17 eyes with uncomplicated cataract surgery. The authors revealed an increase in retinal thickness and volume in the first few months after the surgery, which was followed by a spontaneous decline in these parameters in the subsequent 12 months postop.…”
Section: Fig 2 Example Of a Patient Showing Upregulation Of Retinal F...supporting
confidence: 85%
See 1 more Smart Citation
“…Even though cataract surgery is highly effective and implantation of an artificial lens eliminates the possibility of refractive changes, unfortunately, diabetic patients are at a higher risk of intraoperative and postoperative complications compared to non-diabetic patients [ 29 , 30 ]. It has been shown that phacoemulsification in diabetic patients can lead to a relatively rapid progression of diabetic retinopathy, accelerate vitreous hemorrhage [ 31 ], and increase the thickness of the central retina [ 32 ]. Even uncomplicated cataract surgery leads to an increase in the concentration of inflammatory cytokines, vascular endothelial growth factor (VEGF), hepatocyte growth factor, interleukin-1 (IL-1), and pigment-epithelium-derived factor [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent OCTA studies addressing macular perfusion after uncomplicated phacoemulsification reached conflicting results [ 11 , 21 , 22 ]. Although conducted on a relatively large number of subjects (N = 107, N = 58, and N = 44), cataract density was assessed subjectively [ 11 , 21 ] or was not assessed at all [ 22 ], different OCTA devices were used, no analysis of QI and EA parameters before and after phacoemulsification was performed, while the subjects had lower preoperative BCVA compared to our study. The above settings could all be raised as potential sources of bias that may significantly influence quantitative measurements and confound the outcomes.…”
Section: Discussionmentioning
confidence: 99%